Establishment and validation of a simple and accurate qPCR detection method for Haemophilus parasuis - Jin, Hui; Xiao, Xingyu; Wang, Jingnan; Wang, Zhihao; Wei, Shuqin; Dong, Changying; Zhang, Yongzhe; Kang, Chunyang; Sun, Yajuan (Scientific reports, 2025)
As an infectious disease that poses a significant threat to the rapidly growing pig breeding industry, the detection of Haemophilus parasuis (HPS) is often compromised by various interfering substances present in the test sample during quantitative real-time PCR (qPCR). The rapid detection of HPS is important for the isolation of infectious pigs and their treatment. We designed and optimized a rapid qPCR test to detect the INFB gene of HPS in clinical and environmental samples on pig farms. The method was evaluated for its specificity, sensitivity, repeatability, anti-interference capability, and its ability to detect HPS in clinical samples. The results indicated that the method was specific for the detection of HPS when evaluated against pathogens and intestinal probiotics found in pig farms. By using a seven-fold dilution series of the recombinant plasmid DNA in triplicate, it was determined that the lowest limit of detection (LOD) for this method was less than 10 copies/µL. The results of inter-batch and intra-batch repeatability tests showed that the coefficient of variation (CV) was consistently below 1%. Furthermore, the impact of 14 endogenous and exogenous interfering substances on the Ct values detected by the HPS qPCR was found to be less than 5% when compared to the Ct values obtained in the absence of interfering substances. A total of 248 clinical samples were analyzed using the HPS qPCR, commercial kits, and corresponding national standards, yielding positive rates of 9.27%, 6.05%, and 9.27%, respectively. Notably, the positive and negative percent agreement between the detection method developed in this research and the national standard was 100%. These findings demonstrate that the established detection method is suitable for epidemiological research on HPS and for diagnosing clinical samples containing interfering substances, thereby providing essential technical support for the prevention and control of HPS.